Developing Methodological Tools to Estimate Efficiency of Research Organization Divisions - E. A. Grigoreva (Вестник Российского экономического университета имени Г. В. Плеханова)
Appraisal of any organization efficiency is an important element of detail studying the key indicators of business activity. As a rule such appraisal is based on the whole set of standard quantitative indices. Today there are no reliable methodological tools to estimate efficiency of research organization divisions, which could allow us to identify real problems and therefore to enhance their work. A lot of methods for estimating organization efficiency were proposed, however the majority of them do not take into account specific features of research organization and their division functioning. Due to this fact, we face the necessity to work out the system of key indicators, which could provide a general idea about the divisions’ standing and their possible problems and give an opportunity to control attaining the set goals. The author elaborated methodology of assessing the efficiency of research organization division work based on expert appraisal of indices of both quantitative and qualitative analysis.